Multifaceted link between cancer and inflammation - Sethi, G.; Shanmugam, M.; Ramachandran, L.; Kumar, Alan Prem; Tergaonkar, V. (2012)
Increasing evidence from epidemiological, preclinical and clinical studies suggests that dysregulated inflammatory response plays a pivotal role in a multitude of chronic ailments including cancer. The molecular mechanism(s) by which chronic inflammation drives cancer initiation and promotion include increased production of pro-inflammatory mediators, such as cytokines, chemokines, reactive oxygen intermediates, increased expression of oncogenes, COX-2 (cyclo-oxygenase-2), 5-LOX (5-lipoxygenase) and MMPs (matrix metalloproteinases), and pro-inflammatory transcription factors such as NF-κB (nuclear factor κB), STAT3 (signal transducer and activator of transcription 3), AP-1 (activator protein 1) and HIF-1α (hypoxia-inducible factor 1α) that mediate tumour cell proliferation, transformation, metastasis, survival, invasion, angiogenesis, chemoresistance and radioresistance. These inflammation-associated molecules are activated by a number of environmental and lifestyle-related factors including infectious agents, tobacco, stress, diet, obesity and alcohol, which together are thought to drive as much as 90% of all cancers. The present review will focus primarily on the role of various inflammatory intermediates responsible for tumour initiation and progression, and discuss in detail the critical link between inflammation and cancer.